2020
DOI: 10.1186/s12879-020-05567-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of surgical site infection following colorectal surgery in China: a national cross-sectional study

Abstract: Purposes Surgical site infection (SSI) after colorectal surgery is a frequent complication associated with the increase in morbidity, medical expenses, and mortality. To date, there is no nationwide large-scale database of SSI after colorectal surgery in China. The aim of this study was to determine the incidence of SSI after colorectal surgery in China and to further evaluate the related risk factors. Methods Two multicenter, prospective, cross-sectional studies covering 55 hospitals in China and enrolling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
4
16
2
Order By: Relevance
“…An interesting relationship observed in this study was that with increasing age (over 60 years) the risk of developing SSI decreases, although this relationship was not signi cant. In the study of Tie-Ying et al [24], similar to the result of our research, such a result was obtained. Our study showed that the type of intervention for colon cancer was signi cantly associated with SSI, so that patients who had segmental resection with anastomosis had more than twice the risk of SSI compared to patients who had right hemicolectomy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…An interesting relationship observed in this study was that with increasing age (over 60 years) the risk of developing SSI decreases, although this relationship was not signi cant. In the study of Tie-Ying et al [24], similar to the result of our research, such a result was obtained. Our study showed that the type of intervention for colon cancer was signi cantly associated with SSI, so that patients who had segmental resection with anastomosis had more than twice the risk of SSI compared to patients who had right hemicolectomy.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have shown that the incidence of SSI was higher in people with diabetes, but this incidence was not statistically signi cant in diabetic patients [24,25,[33][34][35]. However, our study found that having diabetes signi cantly increased the risk of developing SSI more than doubled.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The specific enumeration of comorbid conditions indicated that the most common chronic diseases consisted of a major part of the comorbidities in elderly patients with hip fracture. Additionally, chronic respiratory disease, diabetes mellitus, hypertension, and cerebrovascular disease, which were the top five most frequent, have been found to be associated with post-operative infection in both the surgical site and other organs [14,18,20,27,35,36]. Moreover, some diseases which were not in the top five most frequent, such as anemia, malignant tumour, and cardiac failure, have also have been found to be associated with post-operative infections [35,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by the studies of Zhang et al and Alkaaki et al, which reported that emergency surgeries had a fivefold increase in the risk of development of SSI compared to elective surgeries. This could be explained by the lack of bowel prep in emergency colorectal surgeries, thus, increasing the likelihood of bacterial translocation [5,14].…”
Section: Discussionmentioning
confidence: 99%